Emergency Peripartum Hystrectomy and Postnatal Depression - Khalid, Tabinda; Nawaz, Sobia; Ahmed, Malik Irfan; Malik, Saima Nawaz; Salim, Ruqyyah; Manzoor, Shahla (Journal of Rawalpindi Medical College, 2023)
Objective: to investigate postnatal depression after emergency peripartum hysterectomy versus controls. Material and methods: This case control study was conducted at District headquarters teaching hospital Rawalpindi between July 2020 and June 2021.We compared postnatal depression among patients who underwent emergency peripartum hysterectomy (EPH)versus control group where surgical procedures other than hysterectomy (B-Lynch, uterine artery ligation or internal iliac artery ligation) were performed. Results: A total of 88 patients were included, 44 in hysterectomy group and 44 in non hystrectomized/control group. The scores on Edinburgh post-natal depression scale were high in hysterectomy group (11.61±2.48) , compared to non hysterectomy group(6.79±2.13) which was statistically significant. ( p=0.001).Uterine atony, Placental abruption, placenta previa and accrete, were identified as main reasons for surgical intervention in both groups. Emergency peripartum hysterectomy is a traumatic birth event with serious physical, emotional and psychological consequences. It is empirical to not only screen the women in immediate postpartum period, but a long term follow up in community is required.